Genetically Determined Serum Calcium Levels and Markers of Ventricular Repolarization: A Mendelian Randomization Study in the UK Biobank. (June 2021) - Young, William J.; Warren, Helen R.; Mook-Kanamori, Dennis O.; Ramírez, Julia; van Duijvenboden, Stefan; Orini, Michele; Tinker, Andrew; van Heemst, Diana; Lambiase, Pier D.; Jukema, J. Wouter; Munroe, Patricia B.; Noordam, Raymond
Abstract : Background: ECG markers of ventricular depolarization and repolarization are associated with an increased risk of arrhythmia and sudden cardiac death. Our prior work indicated lower serum calcium concentrations are associated with longer QT and JT intervals in the general population. Here, we investigate whether serum calcium is a causal risk factor for changes in ECG measures using Mendelian randomization (MR). Methods: Independent lead variants from a newly performed genome-wide association study for serum calcium in >300 000 European-ancestry participants from UK Biobank were used as instrumental variables. Two-sample MR analyses were performed to approximate the causal effect of serum calcium on QT, JT, and QRS intervals using an inverse-weighted method in 76 226 participants not contributing to the serum calcium genome-wide association study. Sensitivity analyses including MR-Egger, weighted-median estimator, and MR pleiotropy residual sum and outlier were performed to test for the presence of horizontal pleiotropy. Results: Two hundred five independent lead calcium-associated variants were used as instrumental variables for MR. A decrease of 0.1 mmol/L serum calcium was associated with longer QT (3.01 ms [95% CI, 2.03 to 3.99]) and JT (2.89 ms [1.91 to 3.87]) intervals. A weak association was observed for QRS duration (secondary analyses only). Results were concordant in all sensitivity analyses. Conclusions: These analyses support a causal effect of serum calcium levels on ventricular repolarization, in a middle-aged population of European-ancestry where serum calcium concentrations are likely stable and chronic. Modulation of calcium concentration may, therefore, directly influence cardiovascular disease risk. Abstract : Supplemental Digital Content is available in the text.